The psychometric properties of the grazing questionnaire in an obesity sample with and without binge eating disorder - Dean Spirou; Jayanthi Raman; Mimi Leith; James Collison; Ramy H. Bishay; Golo Ahlenstiel; Phillipa Hay; Evelyn Smith (Journal of Eating Disorders, 2022)
Abstract Background Despite being the first validated measure of grazing, the Grazing Questionnaire (GQ) has not been investigated among individuals with obesity. Therefore, the current study aimed to examine the psychometric properties of the GQ in an obesity sample. Methods Participants (N = 259) were recruited from community and clinical settings in Australia. The sample comprised adults with normal weight (n = 77) and obesity (n = 182). A portion of individuals with obesity (n = 102) had binge eating disorder (BED). Data from the obesity group was examined to establish the factor structure, validity, and reliability of the GQ. A one-way ANOVA with planned contrasts was conducted to compare scores on the GQ across groups. Results Confirmatory factor analysis revealed that the 2-factor model of the GQ was the best model fit for individuals with obesity. The GQ demonstrated high internal consistency, test–retest reliability over 3 months, and convergent and divergent validity. As hypothesised, the obesity group had significantly higher scores on the GQ than the normal weight group, while the obesity with BED group had significantly higher scores than the obesity without BED group. Conclusion This was the first study to investigate the psychometric properties of the GQ in an obesity sample. Overall, findings indicated that the GQ is a psychometrically sound measure of grazing among individuals with obesity. These findings provide further support for two distinct subtypes of grazing and highlight the importance of increased assessment and management of grazing behaviours for individuals with obesity and eating disorders. Plain English summary Maintaining a healthy weight is one of the greatest challenges for individuals with obesity. Certain eating patterns such as grazing may contribute to difficulties in weight management. Grazing is the repetitive and unplanned eating of small amounts of food that is not related to feeling hungry. Researchers and clinicians often use self-report questionnaires to measure grazing. However, the first validated questionnaire of grazing has not been investigated among individuals with obesity. Therefore, the goal of this study was to examine and validate the Grazing Questionnaire in individuals with obesity. Overall, our results showed that the Grazing Questionnaire is a valid and reliable self-report measure of grazing in individuals with obesity. Similar to previous research, we found that there are two subtypes of grazing. The first subtype involves continuous, unplanned eating. The second subtype is associated with a sense of loss of control over eating. We also found that people with obesity and binge eating disorder graze more than people with obesity that do not have binge eating disorder, while both groups graze more than individuals with normal weight. We recommend that clinicians routinely assess and treat unhelpful grazing patterns when working with individuals with obesity and eating disorders.